Stock-Price Manipulation - Allen, Franklin; Gale, Douglas (Review of Financial Studies, 1992)
It is generally agreed that speculators can make profits from insider trading or from the release of false information. Both forms of stock-price manipulation have now been made illegal. In this article, we ask whether it is possible to make profits from a different kind of manipulation, in which an uninformed speculator simply buys and sells shares. We show that in a rational expectations framework, where all agents maximize expected utility, it is possible for an uninformed manipulator to make a profit, provided investors attach a positive probability to the manipulator being an informed trader.